Histomorphometric evaluation of different grafting materials used for alveolar ridge preservation: a systematic review and network meta-analysis. Issue 6 (June 2020) - Canellas, J.V.d.S.; Ritto, F.G.; Figueredo, C.M.d.S.; Fischer, R.G.; de Oliveira, G.P.; Thole, A.A.; Medeiros, P.J.D.
Abstract: In this systematic review and network meta-analysis including only randomized clinical trials (RCTs), different grafting materials used in alveolar ridge preservation after tooth extraction were analysed, focusing on histomorphometric new bone formation (NBF) in core biopsies obtained during implant placement. The PubMed, Embase, Cochrane Library, Web of Science, Scopus, and LILACS databases, as well as the grey literature, were searched for published and unpublished trials (from database inception to January 14, 2019). The primary outcome was the percentage of NBF. The secondary outcomes were the percentage of residual biomaterial and the percentage of soft tissue. An arm-based network meta-analysis was performed. The rank of intervention efficacy was obtained to measure the probability of each biomaterial being ranked first across all interventions. A total of 1526 studies were found, of which 38 were included for quantitative analysis. Three trials were rated as having a high risk of bias and 35 trials as having an unclear risk of bias. The network meta-analysis showed that nine grafting materials decreased NBF and 25 did not decrease NBF. The grafting material with the highest amount of NBF was plasma rich in growth factors. Due to the lack of studies with a low risk of bias, further RCTs are needed for definitive conclusions.